DESARROLLO DE PORTAFOLIO DIGITAL PARA OPTIMIZAR LA GESTION BIBLIOTECARIA EN LA I.E.P AVANTGARD COLLEGE – SEDE HUAURA - 2021 - Changana Torres, Juan Bernardo (2022)
The research conducted, which is entitled, "Development of digital portfolio to optimize library management in the IEP Avant Gard College Huaura 2021, the educational institution, in times of pandemic faces infinite problems that affect the teaching of students, one of them is the use of books of importance with what the institution has (Mathematics Singapore, Cambridge, etc.), according to health safety regulations, it is impossible for the student to enter closed spaces such as the library and especially to attend the educational centers. ), according to health safety regulations, it is impossible for the student to enter closed spaces such as the library and above all to attend the educational centers, and the most important problem facing the institution, is the poor management of the management of books and the areas involved, so it is essential a computer solution to help optimize the processes in a more appropriate way. To achieve this purpose, the work was arranged through a software development model, and the use of the XP methodology, which will be used for the development of the product as a result of the research, having as pillars of choice the PHP programming languages and MySQL database manager, with the help of technological applications such as Bootstrap, JavaScript, among others that will help us to better integrate the final product. KEYWORDS: Software, XP methodology, quantitative, experimental, descriptive, MySQL, PHP, modeling.